Neuromuscular fatigue of the knee extensors during repeated maximal intensity intermittent‐sprints on a cycle ergometer. Issue 4 (11th February 2015) - Pearcey, Gregory E.P.; Murphy, Justin R.; Behm, David G.; Hay, Dean C.; Power, Kevin E.; Button, Duane C.
ABSTRACT: Introduction : We studied the time course of neuromuscular fatigue during maximal intensity intermittent‐sprint cycling. Methods : Eight participants completed 10, 10‐s sprints interspersed with 180 s of recovery. The power outputs were recorded for each sprint. Knee extensor maximum voluntary contraction (MVC) force, voluntary activation, and evoked contractile properties were recorded presprint, postsprint 5, and postsprint 10. Results : Total work over the 10 sprints decreased significantly ( P  < 0.05) and could be described by 2 linear relationships from sprints 1–5 compared with sprints 6–10. Participants had significantly ( P  < 0.05) lower MVC and twitch forces postsprint 5 compared with presprint. MVC, voluntary activation, and twitch force were decreased ( P  < 0.05) postsprint 10 compared with postsprint 5. Conclusions : The maximal intermittent sprints induced neuromuscular fatigue. Neuromuscular fatigue in the first 5 sprints was mainly peripheral, whereas in the last 5 sprints it was both peripheral and central. Muscle Nerve 51: 569–579, 2015